2017
DOI: 10.1007/s11325-017-1500-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of obstructive sleep apnea in morbidly obese patients undergoing bariatric surgery

Abstract: Obstructive sleep apnea is frequently observed in morbidly obese patients undergoing bariatric surgery and the severity tends to be severe. Snoring, STOP-Bang score ≥ 3, fatty liver, and BMI were significantly correlated with OSA. Dyslipidemia and BMI were demonstrated to be associated factors for severity of OSA in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
1
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 12 publications
2
11
1
5
Order By: Relevance
“…Obesity is recognized as a major risk for OSA and its prevalence is higher than 60% in the bariatric surgery population [40,41]. However, in this study, we found a lower prevalence of OSA (27%).…”
Section: Discussioncontrasting
confidence: 68%
“…Obesity is recognized as a major risk for OSA and its prevalence is higher than 60% in the bariatric surgery population [40,41]. However, in this study, we found a lower prevalence of OSA (27%).…”
Section: Discussioncontrasting
confidence: 68%
“…About 96% of our study population had OSA and about 75% were considered to have OSA of moderate or severe degree. The prevalence of OSA in the bariatric surgery population has been previously reported in the range 71% to 91% which means that our prevalence is in the upper level [18,3133] probably depending on differences in study population composition. Our high prevalence number of OSA highlights the importance of screening for OSA.…”
Section: Discussionmentioning
confidence: 77%
“…The high prevalence of OSA is also expected due to the considerable frequency of obese people in this population (62.5%). The prevalence of apnea in obese individuals is increased, reaching 85.7% in obese class III patients who are awaiting bariatric surgery 40 .…”
Section: Discussionmentioning
confidence: 99%